NATIONAL ACCOUNTING MATRIX WITH ENVIRONMENTAL ACCOUNTS (NAMEA) - AN OVERVIEW OF ENVIRONMETALLY EXTENDED INPUT-OUTPUT ANALYSIS - Gajos, Edyta; Prandecki, Konrad (Acta Scientiarum Polonorum. Oeconomia, 2016)
Increasing human pressure on the environment results in the need for tools to precise identification of the environmental damage source. Environmentally-extended input- output analysis (EEIO) is an answer for that demand. National accounting matrix with environmental accounts (NAMEA) is one of the attempts to create complete EEIO tables. The aim of the paper is to present NAMEA tables as an useful source of data and tool which allows to conduct environmentally-extended input-output analysis in relation to environmental policy. NAMEA tables show emission data per sector. The aim of it is to integrate environmental data with data on economic activity as recorded in the National Accounts framework. NAMEA tables are a useful data source and tool for both environmental policy and another economic studies and researches.